A descriptive cross-sectional study on knowledge of Hand washing among health professionals in a medical college - Keyal, Niraj Kumar; Singh, Alok Kumar; Chaudhary, Pankaj; Ansari, MD Safroz; Khanal, Sudesh (Birat Journal of Health Sciences, 2022)
Introduction: Nosocomial infection is common due to poor practice of hand hygiene. There is a variation in the level of knowledge of handwashing among different health professionals. Objectives: The aim of the study was to assess the basic knowledge of handwashing among health professionals. Methodology: This cross-sectional study was done in 370 healthcare professionals like doctors, nurses, health assistants of a National medical college. The questionnaire used was adapted from the World Health Organization about hand hygiene knowledge for health professionals. There were 18 questions assessing the basic knowledge and practice of handwashing. The level of hand hygiene knowledge was calculated by dividing the responses into four groups based on score more than 90% as excellent, 75-90% considered as good, 50-74% moderate, and less than 50% considered as low.. All data was transferred to the excel sheet and transferred to a statistical package for the social sciences-17. The result was presented using frequency tables, graphs, and charts. Result: Out of 370 participants, 318(85.9%) were females, and 52(14.1%) males. The mean age was 24.59±4.48 years. Of all the respondents, 24% had low, 30% moderate, 26% good, and 21% had excellent knowledge of hand hygiene. In terms of practice, only 34% had a moderate level of practice of hand hygiene. Conclusion: Regular training and re-training through simulations of hand hygiene will lead to an improvement in the knowledge and practice of handwashing.